Building an Effective Climate Regime While Avoiding Carbon and Energy Stalemate - Wara, Michael (Columbia Journal of Environmental Law, 2019)
The world needs a new approach to achieving international progress on climate change. Despite prodigious diplomatic efforts over two decades aimed at limiting emissions of climate change pollutants, relatively little in the way of effective global governance has been achieved. This lack of progress has led some, including the U.S. government, to seek climate deals outside of the climate negotiations, leading to fragmentation of the Climate Regime. In Part II, I present one of the key dilemmas faced by U.S. climate negotiators over the past decade—whether to pursue reductions of a super-greenhouse gas within the Ozone Regime or within the Climate Regime. In Part II, I also argue that this dilemma is a symptom of a larger problem—the structure of climate negotiations. The negotiations currently place a narrow legal, economic, and political focus on the hardest part of the climate change problem—energy-related carbon dioxide emissions. This focus developed due to scientific understanding of climate at the time that legal and policy frameworks were put in place. However, scientific developments since then have significantly undercut the view that carbon and energy should be the sole focus of efforts to avoid climate change. Part III explains key scientific developments over the past two decades and how these have reshaped the scientific view of human impacts on climate. Studies aimed at resolving the remaining uncertainties in climate projections have resulted in a dramatically improved understanding of the importance of short-lived climate pollutants in causing current and medium-term climate change. This new science justifies a shift away from legal and policy frameworks that focus on energy and carbon dioxide emissions towards more flexible frameworks that aim to produce meaningful reductions in other, shorter-lived global warming pollutants. In Part IV, I argue that such a shift in focus could produce more effective outcomes. Developed and developing countries have much more experience in abatement of short-lived pollutants than carbon dioxide. Also, focus on short-lived pollutants often leads to near-term air pollution-related benefits that will help to change the cost-benefit calculus and improve the political acceptance of greenhouse gas reductions. Abatement of short-lived pollutants is something we know how to do and which creates benefits that can be captured today by the countries that undertake it, while still reducing the risks of climate change. In Part V, I provide an account of how short-lived climate pollutants might form a path toward more comprehensive international greenhouse gas limits in the future. Near-term international success with short-lived pollutants might generate a cooperative multilateral dynamic within the broader Paris Agreement framework. Parties can improve and consolidate their climate change related reputations for compliance using short-lived climate pollutants, increasing the likelihood of more costly agreements on carbon dioxide. This new process, the reputations for compliance it would generate, and the robust institutions that result from it are a necessary, but currently lacking, precondition of any global agreement to limit energy-related carbon emissions. While other authors have suggested pursuit of reductions in short-lived pollutants via bilateral or plurilateral approaches, or outside of the Climate Regime, only the multilateral Climate Regime as implemented within the Paris Agreement framework is likely to provide the legitimacy as well as the financial resources necessary for deep and effective cuts in carbon dioxide emissions. Short-lived climate pollutants provide a path forward to deepening strategic cooperation on climate. Thus rather than cutting deals outside of the Climate Regime, the United States should seek to bring agreements for deep cuts of super-greenhouse pollutants inside it—as much for their strategic as their environmental benefits.